Definition of electrical parameters of asynchronous motors in transitive modes applying quasi-balanced method - Burbelo, M. Y.; Hadai, A. V.; Havryliuk, V. V.; Barchuk, V. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Spectral values and quasi-balanced method are used for definition of parameters of asynchronous motors during electromechanical transients.